Isan Culture: Naming of Monkan Kankoon’s Songs - Phonkaewket, Anantasak; Kasemsuksamran, Cherry; Fongrit, Mettar; Sonjan, Chanyuth; Sutthipunyo, Chomboon; Thipphana, Santi; Muangyen, Neungreuthai (Dhammathas Academic Journal, 2023)
The objective of this article is to examine the Isan culture that emerged from the name of Monkan Kankoon’s songs. By reviewing all Monkan Kaenkoon’s song titles, 66 songs with names associated with culture, tradition, belief, and way of life were identified to be used as data for the analytical study as follows. 1. Culture is divided into four categories: 1) Isan language culture discovered 50 songs, accounting for 75.75 percent of the total. 2) Dressing culture, 1 song discovered, representing 1.51 percent 3) Folk performance culture discovered 3 songs representing 4.54 percent, and 4) Isan place name culture discovered 5 songs representing 7.57 percent. 2. Tradition was represented by 4 songs, accounting for 6.06 percent of the total. 3. There were 4 songs for belief, accounting for 6.06 percent. 4. The way of life was represented by 13 songs, accounting for 19.69 present of the total.